Effect of combined periodontal and orthodontic treatment of tilted molars and of teeth with intra‐bony and furcation defects in stage‐IV periodontitis patients: A systematic review. (10th November 2021) - Kloukos, Dimitrios; Roccuzzo, Andrea; Stähli, Alexandra; Sculean, Anton; Katsaros, Christos; Salvi, Giovanni E.
Abstract: Aim: To assess the effect of combined periodontal and orthodontic treatment (OT) in stage‐IV periodontitis patients. Materials and methods: Three focused questions were addressed using the Population, Intervention, Comparison, Outcome, and Study Design criteria. Randomized controlled trials (RCTs), controlled clinical trials, follow‐up studies, case series, and controlled/uncontrolled before/after studies were assessed for inclusion. Primary outcomes included mean changes in pocket probing depth (PPD) and clinical attachment level (CAL). Qualitative synthesis of results was performed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Results: Out of 916 records, 1 retrospective case series study reported the effect of OT of tilted molars, 2 RCTs and 10 prospective and 2 retrospective case series studies reported the effect of OT of treated intra‐bony defects and 0 articles reported the effect of OT of treated furcation defects. Mean PPD changes were reported in 14 articles, and mean CAL changes were reported in 8 articles. Risk of bias was high in both included RCTs, critical in nine articles, and serious in four articles. No articles included patient‐reported outcomes, and three articles reported harms/adverse effects. Conclusions: Evidence is limited by (i) the lack or low number of included studies, (ii) the apparent methodological and clinical heterogeneity, and (iii) the high risk of bias of the retrieved studies. No solid conclusions could be drawn concerning OT in stage‐IV periodontitis patients with respect to tilted molars, teeth with treated intra‐bony defects, and teeth with treated furcation defects.